Clinical Application of Metagenomic Next-Generation Sequencing for Suspected Infections in Patients With Primary Immunodeficiency Disease - Tang, Wenjing; Zhang, Yu; Luo, Chong; Zhou, Lina; Zhang, Zhiyong; Tang, Xuemei; Zhao, Xiaodong; An, Yunfei (Frontiers in Immunology, 2021)
Background: Infections are the major cause of morbidity and mortality in patients with primary immunodeficiency disease (PID). Timely and accurate microbiological diagnosis is particularly important in these patients. Metagenomic next-generation sequencing (mNGS) was been used for pathogen detection recently. However, few reports describe the use of mNGS for pathogen identification in patients with PID. Objective: To evaluate the utility of mNGS for detecting pathogens in patients with PID, and to compare it with conventional microbiological tests (CMT). Methods: This single center retrospective study investigated the diagnostic performance of mNGS for pathogens detection in PID patients and compared it with CMT. Sixteen PID patients with suspected infection were enrolled, and medical records were analyzed to extract detailed clinic characteristic such as gene variation, immune status, microbial distribution, time-consuming of mNGS and CMT, treatment, and outcomes. Results: mNGS identified pathogenic microbe in 93.75% samples, compared to 31.25% for culture and 68.75% for conventional methods, and detected an extra 18 pathogenic microorganisms including rare opportunistic pathogens and Mycobacterium tuberculosis. Pathogen identification by mNGS required 48 hours, compared with bacterial culture for 3-7 days and even longer for fungus and Mycobacterium tuberculosis culture. Conclusions: mNGS has marked advantages over conventional methods for pathogenic diagnosis, particularly opportunistic pathogens and mixed infections, in patients with PID. This method might enable clinicians to make more timely and targeted therapeutic decisions, thereby improving the prognosis of these patients.